2015
DOI: 10.1149/2.0471507jes
|View full text |Cite
|
Sign up to set email alerts
|

Passivity of Dual-Phase Carbon Steel with Ferrite and Martensite Phases in pH 8.4 Boric Acid-Borate Buffer Solution

Abstract: Passivity of a dual-phase carbon steel with ferrite and martensite phases was investigated in pH 8.4 boric acid-borate buffer solution. The corrosion potential of the dual-phase steel was higher than that of pure martensitic steel and lower than that of pure ferritic steel. In dynamic polarization measurements, the passivity-maintaining current of the dual-phase steel was an intermediate value of those of pure ferritic and martensitic steels. EIS revealed that both the charge transfer resistance and capacitanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 34 publications
4
13
0
Order By: Relevance
“…One group has suggested that the low density of point defect causes high corrosion resistance. Extensive experimental results apparently agree with this opinion [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Other researchers have reported a high corrosion rate or a low corrosion resistance for the metals or alloys with passive films with low point defect density [38][39][40][41][42], corresponding to the results drawn from this work.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…One group has suggested that the low density of point defect causes high corrosion resistance. Extensive experimental results apparently agree with this opinion [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Other researchers have reported a high corrosion rate or a low corrosion resistance for the metals or alloys with passive films with low point defect density [38][39][40][41][42], corresponding to the results drawn from this work.…”
Section: Resultssupporting
confidence: 87%
“…Therefore, the origin of such discordance is not yet known. Many of the reports included a proposition that the concentration of point defect would affect the stability of the passive film and hence the corrosion resistance but did not provide a mechanism supported theoretically [18,19,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Resultsmentioning
confidence: 99%
“…The donor densities of both FM and FP samples are on the order of 10 21 cm −3 . This order of magnitude is typical for disordered heavily doped passive films [5,9,18,21]. The donor density values have been calculated from the slopes in the more positive potential range, i.e., for E > −0.3 V. The donor densities of passive films are 2.4 ± 0.3 × 10 21 cm −3 for the FM and 1.49 ± 0.08 × 10 21 cm −3 for the FP sample.…”
Section: Electrochemical Characterisation Of the Passive Layermentioning
confidence: 99%
“…The role of pearlite and martensite in combination with ferrite in two-phase steels on mechanical properties is understood relatively well [2,3]. However, their corrosion and passivity behaviour is not yet well understood [4,5]. This is mainly due to the complex interaction of the microstructural features-grain sizes, phase fractions, dislocation densities, crystallographic orientations, phase morphologiesdictating the properties of the passive layer of steels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation